Marxism and the Leninist Revolutionary Model - Davidshofer, W. author. aut Link
XI, 191 p.
Keywords: This book explores Marxist and Leninist revolutionary theory. Topics include: the philosophical dialectic, historical materialism, the revolutionary movement, and Communist cadre political rule in the socialist state. Emphasis on Lenin's wartime political treatment of imperialism, national self-determination, and socialism in one country.